1993
DOI: 10.7589/0090-3558-29.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Serological Evidence of Coxiella burnetii Infection in Wild Animals in Japan

Abstract: One hundred and thirty-four (26%) of 511 sera from 11 wild animal species in eight prefectures in Japan had antibody titers to Coxiella burnetii by the enzyme-linked immunosorbent assay. High prevalences were observed in Japanese black bears (Ursus thibetanus) (78%), Hokkaido deer (Cervus nippon yesoensis) (69%), Japanese hares (Lepus brachyurus) (63%), Japanese deer (Cervus nippon centralis) (56%), and to some extent in Japanese monkeys (Macaca fuscata) (28%). A low prevalence (13%) was observed in nutrias (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(31 citation statements)
references
References 6 publications
2
27
0
2
Order By: Relevance
“…In Japan, 16.5% of cats and 11.9% of dogs have been reported to be positive for C. burnetii antibody (6,15). Ejercito et al reported that 11 wild animal species in Japan had antibody to C. burnetii (3). Furthermore, we have found 26% of cattle having the antibody and have isolated C. burnetii from 37% of milk samples of the cattle (unpublished data).…”
Section: Discussionsupporting
confidence: 52%
“…In Japan, 16.5% of cats and 11.9% of dogs have been reported to be positive for C. burnetii antibody (6,15). Ejercito et al reported that 11 wild animal species in Japan had antibody to C. burnetii (3). Furthermore, we have found 26% of cattle having the antibody and have isolated C. burnetii from 37% of milk samples of the cattle (unpublished data).…”
Section: Discussionsupporting
confidence: 52%
“…The only population surveyed in central Portugal could not be associated with any wild ungulate favorability index and was not considered for risk factor analyses. Red deer, roe deer, and wild boar have been found to be infected by C. burnetii previously (36,37,38). No favorability indices for any other potential wild host of C. burnetii are available for the study area.…”
Section: Methodsmentioning
confidence: 99%
“…Em cativeiro estes animais recebem como alimentação uma ração diária semelhante ao dos gatos domésticos e furões. Eles possuem hábitos noturnos, podendo às vezes, ser ativo durante o dia (Labate et al 2001, Rodrigues et al 2007, Bellatine et al 2010, tornando-se veiculadores de zoonoses tais como o vírus da CDV canina (cinomose) (Machida 1993) e Coxiella burnetii (Ejercito et al 1993).…”
Section: Introductionunclassified